Age class of alien tree stands retained for mammal protection have differential effects on flower‐visiting insect assemblages. Issue 6 (9th July 2021) - Adedoja, Opeyemi; Kehinde, Temitope; Samways, Michael J.
Abstract: Limited sunlight reduces plant productivity and foraging activities of pollinators, such as when alien trees shade out native flowering plants. The conservation management response is to remove the impoverishing effect of the alien tree canopy. However, alien trees can provide benefit for certain species when they provide significant scarce resources. We assess how flower‐visiting insects respond to shading from young, small‐sized, open canopy vs. mature, tall, closed‐canopy alien pine trees retained specifically as refuges for certain rare mammals. We sampled flower–visitor species diversity and interactions at various distances from pine stands of both sizes in a matrix of low sclerophyllous natural vegetation. We sampled flower–visitors using coloured pan traps and estimated flower–visitor interactions and flower diversity. Reduction in percentage light reaching the understorey significantly reduced flower abundance, with zero flowers in tall pine understorey. Flower–visitor species composition differed across sampling locations with increasing distance from tall pine understorey. Although pine tree size led to a decline in flower–visitor interaction frequency and network specialisation in all pine tree stands, some bee species that are mostly tree nesters, were observed in unique interactions in association with tall pines only. We show that alien pines, especially tall trees, have an impoverishing effect on flowering plants and flower–visitors. However, these trees also confer benefit to specialised groups such as tree‐nesting bees. While active alien pine removal is encouraged where the trees are actively invading, maintaining well‐contained small stands is of value for two different taxa of conservation concern. Abstract : We assessed flower–visitor diversity and interactions at various distances from small and tall pine trees in a matrix of low sclerophyllous natural vegetation using coloured pan traps and direct observations Increasing pine size led to a decline in flower–visitor abundance and interaction frequency, although some tree nesting bee species were observed in unique interactions in association with tall pines only We show that alien pines, especially tall trees, have an impoverishing effect on flowering plants and flower–visitors. However, these trees also confer benefit to specialised groups such as tree‐nesting bees.